Research on calculation of transverse bending moment of deck of box girder with long-span and long cantilever - Zhaonan Wang; Ruizheng Wang (Scientific Reports)
Abstract To investigate the reasonable calculation value of the transverse design bending moment of a long-span cantilever box girder bridge deck under vehicle load, the plate beam model and beam element frame model were established according to the concept of load effective distribution width in the Chinese highway specifications. The local finite element model and full bridge model of a long-cantilever plate were established using the plate-shell element. The practical calculation formula and finite element analysis of the transverse bending moment of a bridge deck were studied. The results showed that the transverse bending moment of the long-cantilever plate calculated using Baider Bahkt formula slightly deviated from the calculated value of the plate-shell element, and the deviation between the calculated values of Baider Bahkt formula and Sawko formula was 7.72%. Baider Bahkt formula is more accurate than Sawko formula, which is recommended by the Chinese highway specifications.